Influência da chuva após aplicação de imazamox sobre o controle de plantas daninhas aquáticas - de Campos, Caio Ferraz [UNESP]; de Souza, Guilherme Sasso Ferreira [UNESP]; Martins, Dagoberto [UNESP]; Pereira, Maria Renata Rocha [UNESP]; Bagatta, Murilo Villas Boas [UNESP] (My University, 2012)
This study aimed to evaluate the imazamox control efficiency on aquatic plants under different intervals of simulated rain after its spraying. The experiment was carried out in completely random design with four replications. The imazamox at 290.4 g ha-1 was tested on three aquatic weed species, Eichhornia crassipes (Mart.) Solms, Pistia stratiotes L. and Salvinia adnata Desv and, under eight different rain-free periods (0, 2, 4, 6, 8, 12, 24 hours). Rainfall was simulated using a sprinkler irrigation system (20mm). There was a good control of Eichhornia crassipes, regardless of periods without rain after herbicide spraying. However, Pistia stratiotes took a rain-free period of at least eight hours to obtain an effective control. In Salvinia adnata, whole rain-free periods affected the control provided by the herbicide.
Rain influence after imazamox spraying on aquatic weed control
Keywords: Eichhornia crassipes; Herbicide; Macrophyta; Pistia stratiotes; Salvinia adnata